Design of Lightly Loaded Steel Column Base Plates - Murray, Thomas M. (Engineering Journal, 1983)
One of the least-studied structural elements are column base plates. Even less attention has been paid to lightly loaded base plates, defined here as relatively flexible plates of approximately the same size as the outside dimensions of the column supported by the plate. Such base plates are found in low-rise conventional construction and in preengineered metal building applications. In this class of construction, relatively small dead loads and low slope roofs commonly result in uplift loads which must be transferred to the foundation through the base plates. At present, there is no generally accepted practice for the design of such base plates that is not unduly conservative. From results of yield-line analyses and limited supporting experimental data, design procedures for lightly loaded base plates supporting H-shaped columns are proposed. Both concentric axial compression (gravity loading) and concentric axial tension (uplift loading) are considered. Base plate strength for erection safety is also discussed.